2016
DOI: 10.1515/amm-2016-0056
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydrodynamic Structure on Mixing Time of Alloy Additions with Liquid Steel in One Strand Tundish

Abstract: The knowledge of the hydrodynamic pattern aids in designing new and modernizing existing tundishes. The device under examination is an one-strand tundish of a capacity of 30 Mg. Computer simulation of the liquid steel flow, tracer and alloy addition behaviour in turbulent motion conditions was done using the Ansys-Fluent®computer program. The hydrodynamic conditions of steel flow were determined based on the distribution of the characteristics of tundish liquid steel residence time distribution (RTD). The allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Siddiqui and Jha [20] reported that the inflow rate has a significant impact on grade mixing in tundish during sequential castings. Cwudzinski [21] carried out a numerical investigation of flow control devices in tundish to modify the hydrodynamic pattern inside the tundish. It was reported that an adverse influence of stagnant volume could be compensated by active recycle zone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Siddiqui and Jha [20] reported that the inflow rate has a significant impact on grade mixing in tundish during sequential castings. Cwudzinski [21] carried out a numerical investigation of flow control devices in tundish to modify the hydrodynamic pattern inside the tundish. It was reported that an adverse influence of stagnant volume could be compensated by active recycle zone.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that 80% of the old steel grade in the tundish can come out in the first five-six min of the mixed grade slab casting process. In further quest of understanding the hydrodynamic patterns and implementing it to minimize the mixing in the tundish, Cwudziński [21] studied the dispersion of alloys in the melt. The numerical model was developed to find the distribution of the characteristics of tundish, residence time distribution (RTD) and dispersion of alloy in one strand tundish.…”
Section: Introductionmentioning
confidence: 99%